Water and green ammonia recovery from anaerobic digestion effluent by two-stage membrane distillation. (October 2022) - Shi, Mingfei; Xiao, Man; Feng, Liang; Tu, Te; He, Qingyao; Yan, Shuiping
Abstract: A water and green ammonia recovery strategy for anaerobic digestion (AD) effluent treatment through a two-stage membrane distillation (2s-MD) was put forward in this study. In the 1 st -stage, the MAP (monoammonium phosphate solution, NH4 H2 PO4 )/DAP (diammonium phosphate solution, (NH4 )2 HPO4 ) loop, was used as the recyclable ammonia absorbent to recover ammonia from AD effluent. The multicycle ammonia absorption-regeneration experiments illustrated that the ammonia removal efficiency was stable (~81 %) and the recovered ammonia solution was 1.05 mol/L. In the 2 nd -stage, the water recovery experiments from AD effluent with different ammonia concentrations were conducted. The results indicated that the water recovered from ammonia-removed AD effluent could be adopted as the general industrial or agricultural water. Finally, the economic evaluation demonstrated that the application of MAP solution as the recyclable ammonia absorbent was more economically efficient than the sulfuric acid solution. The treatment cost and net profit of AD effluent treatment by 2s-MD were $ 1.73/m 3 and $ 0.83/m 3, respectively. The 2s-MD can be acted as a valuable candidate strategy for sustainable green ammonia and water recovery from AD effluent. Highlights: Water and green ammonia are recovered by two-stage membrane distillation (2s-MD). MAP/DAP loop is used as the recyclable ammonia absorbent for ammonia recovery. Positive net profit is obtained from resource treatment for AD effluent by 2s-MD.